Actividad física y estado nutricional en alumnos de la Escuela Fiscal Mixta 18 de Noviembre y Liceo de Loja. - Ramón Jaramillo, Stephanie Viviana (2017)
Physical activity is essential for a good quality of life, however the high levels of sedentarism, affects the nutritional status especially of schoolchildren. The objectives of this project were: to evaluate the level of physical activity, to determine the nutritional status and to relate the physical activity and the nutritional status of the students of the Fiscal Joint School 18 de Noviembre and Liceo de Loja, period 2016-2017. 380 schoolchildren who met the inclusion criteria participated; the Chilean Physical Activity Questionnaire (INTA) was applied to parents and anthropometric assessment was performed to establish the students' Body Mass Index. Through the quantitative, descriptive cross-sectional study, the following results were obtained: sedentary 58.8%, active 41.3% at school November 18, Liceo de Loja sedentary 65.7% and active 34.3%. Nutritional status, normal 73.3%, overweight 26.3% and obesity 0.4% on November 18; in Liceo de Loja normal 62.9%, overweight 32.1% and obesity 5%. Of the active schoolchildren have normal nutritional status 38.4%, of the sedentary students 31.1% normal and 28.2% are overweight, Pearson chi square (0.020, p <0.05). It can be concluded that there is a statistically significant relationship between physical activity and nutritional status of schoolchildren in this population. Keywords: physical activity, sedentary lifestyle, nutritional status, schooling.